Understanding Temperature‐Dependent Charge Extraction and Trapping in Perovskite Solar Cells. (7th April 2020) - Zhou, Qian; Wang, Boxing; Meng, Rui; Zhou, Jiyu; Xie, Shenkun; Zhang, Xuning; Wang, Jianqiu; Yue, Shengli; Qin, Bing; Zhou, Huiqiong; Zhang, Yuan
Abstract: Understanding the factors that limit the performance of perovskite solar cells (PSCs) can be enriched by detailed temperature ( T )‐dependent studies. Based on p‐i‐n type PSCs with prototype methylammonium lead triiodide (MAPbI3 ) perovskite absorbers, T ‐dependent photovoltaic properties are explored and negative T ‐coefficients for the three device parameters ( V OC, J SC, and FF) are observed within a wide low T ‐range, leading to a maximum power conversion efficiency (PCE) of 21.4% with an impressive fill factor (FF) approaching 82% at 220 K. These T ‐behaviors are explained by the enhanced interfacial charge transfer, reduced charge trapping with suppressed nonradiative recombination and narrowed optical bandgap at lower T . By comparing the T ‐dependent device behaviors based on MAPbI3 devices containing a PASP passivation layer, enhanced PCE at room temperature is observed but different tendencies showing attenuating T ‐dependencies of J SC and FF, which eventually leads to nearly T ‐invariable PCEs. These results indicate that charge extraction with the utilized all‐organic charge transporting layers is not a limiting factor for low‐ T device operation, meanwhile the trap passivation layer of choice can play a role in the T ‐dependent photovoltaic properties and thus needs to be considered for PSCs operating in a temperature‐variable environment. Abstract : The inverse temperature‐dependencies of the photovoltaic parameters in MAPbI3 perovskite solar cells lead to obtaining a peak efficiency of 21.4% at 220 K. These T ‐varied behaviors are related to combined properties of improved interfacial charge extraction, reduced charge trap density, and suppressed nonradiative recombination at lower temperatures.